WORKSHOP MODEL PEMBELAJARAN KOOPERATIF UNTUK PEMBELAJARAN INKLUSIF DI GUGUS I KEC. KOPANG - Setiawan, Heri; Oktaviyanti, Itsna; Saputra, Heri Hadi; Affandi, Lalu Hamdian (Jurnal Interaktif: Warta Pengabdian Pendidikan, 2025)
This community service activity aims to improve the capacity of elementary school teachers in implementing cooperative learning models as a strategy to support inclusive learning. The workshop was conducted by the INOVASI Regional Facilitator team and the University of Mataram in 2019, involving 14 teachers and 7 principals from Cluster I, Kopang District. The results showed an increase in teachers' understanding of the concept of inclusion and their ability to design lesson plans based on cooperative models. Post-workshop monitoring showed that some schools had begun to implement cooperative strategies in the classroom. This activity proves that practice-based training can encourage pedagogical changes that support fair and equal education for all students.